Role of various risk factors in coronary heart disease development among women under 55 (clinico3angiographic and population study) - N. G. Vardugina; E. G. Volkova (Российский кардиологический журнал)
This population and clinical study, including so called «golden standard» - coronaroangiography, analyzed the prevalence and ethiopathogenic role of various risk factors for coronary heart disease (CHD) in women under 55. Total number of participants was 121. The main group consisted of 69 women with CHD, another 52 women formed the control group. The prevalence of arterial hypertension, dyslipidemia, thyroid pathology, anemia, gynecologic diseases and other factors was high in both groups. For the factors assessed, their prevalence and role in CHD ethiopathogenesis was analyzed among individuals with undamaged coronary arteries, coronary atherosclerosis, and unspecific changes like distal damage, spiral vessels, and muscle cross-bridges.